Empowering Students with Discovery Learning in Circle Geometry for Better Problem-Solving - Usmayati, Uum; Gürbüz, Ferit (EDUPEDIA Publisher, 2024)
The objective of discovery-based teaching aids that use circular material is to assist young individuals in improving their mathematics skills. The ADDIE technique, which encompasses analysis, design, development, implementation, and evaluation, is considered during development. The objective of analysis is to ascertain the specific knowledge and skills that students desire to acquire and the most effective methods for instructing them. Learning about the circle and the components that make it up and then applying that knowledge to the problem-solving process is one of the goals. Learning approaches focused on exploration are established during the project's design phase. In order to facilitate learning about the circular notion, visual aids and environments are currently being developed—the development process results in the production of learning modules, student workbooks, and interactive instructional materials. The designs are what determine the final result. The implementation process entails analysing learning, interactions between students, and the materials used in the classroom. Every effective method of evaluation incorporates the results of student learning as well as input from both the instructor and the students. This strategy aims to discover problems with the quality of the course content. According to the findings of several studies, students who participate in discovery-based training demonstrate improvements in their understanding of circles and their ability to solve mathematical problems on their own. Involving kids in the learning process makes it more exciting and enjoyable.